Seleção de materiais e design: um método com base nas redes neurais artificiais - Nunes, Tercia Valfridia Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study is part of a globalized environment in which companies invest in innovations in search of differention in order to stand out from competittors. This differentiation is an important component material selection, because to create a product to compete with the existing ones is necessary to innovate in materials, design and manufacturing processes. However, the development of a product designers require extensive knowledge of the materials and manufacturing processes. It is worth mentioning the design, as an important considerations in the design process and that this has had a growing involvement in the design of multidisciplinary teams. In addition, it should be noted that Ashby & Johnson (2011) confirm that there is plenty of support for teaching materials in design; an Kindlein et al. (2006) define it as just a basic contact, the relationship that designers have with science and tecnology materials at graduation. In this context, the objective of this work is to propose a method based on the technique of Artificial Neural Networks to design and evaluate a model for predicting the materials and industrial processes to assist the designer in material selection in product design. The aim is to materialize the result of aplying the method proposed in a Microsoft Excel 2010 spreadsheet able to replicate the trained and validated neural network model. In this tool, based on predetermined attributes, manufactuing processes and materials compatible with the required use and based on predetermined attributes options will be provided. It is expected to obtain as output variables, options to address the type of material and the associated manufacturing process, considering predetermined attributes as input variables. Search up with that on the one hand offer the student and/or professional design options appropriate to the type of product to be designed and on the other to optimize the search of materials for product design

Este estudo se insere em um ambiente globalizado no qual as empresas investem em inovação em busca de diferenciação, a fim de se destacar perante os concorrentes. Essa diferenciação tem como importante componente a seleção de materiais, pois para criar um produto em condições de competir com os já existentes é necessário inovar nos materiais, design e processos de fabricação. O desenvolvimento de um produto, portanto, exige dos projetistas amplo conhecimento dos materiais e processos de fabricação. Ressalta-se o design, como elemento relevante do projeto nesse processo e que tem exercido uma crescente participação nas equipes multidisciplinares de projeto. Além disso, convém destacar que Ashby & Johnson (2011) ratificam que não há abundância de suporte para o ensino de materiais na área de design; e Kindlein et. al. (2006) definem como apenas um contato básico, a relação que os definem como apenas um contato básico, a relação que os designers tem com a ciência e tecnologia de materiais na graduação. Nesse contexto, o objetivo deste trabalho é propor um método com base na técnican das Redes Neurais ritificiais para estruturar e avaliar um modelo de previsão dos materiais e processos industriais a fim de auxiliar designer na seleção de materiais no projeto de produtos. Pretende-se materializar o resultado da aplicação do MÉTODO proposto em uma planilha do Microsoft Excel 2010 capaz de replicar o modelo de rede neural treinado e validado. Nesta ferramenta, a partir de atributos pré-determinados, serão fornecidas opções de materiais e processos de fabricação compatíveis com o uso requerido e com base em atributos pré-estabelecidos. Espera-se obter como variáveis de saída, opções que abordem o tipo de material e o processo de fabricação associado, considerando atributos pré-estabelecidos como variáveis de entrada. Busca-se com isso por um lado oferecer ao estudante e/ou profissional de...
Keywords: Desenho industrial; Materiais - Seleção; Processo decisorio; Redes neurais (Computação); Industrial design